Optimizing Educational Service Management to Attract New Students: A Qualitative Study at SMP 3 Tanjungsiang - Mochamad Surya, Candra (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study explores the management of educational services as a strategy to attract new students at SMP 3 Tanjungsiang, a junior high school situated in a mountainous area. Modern education focuses not only on quantitative measures, such as student enrollment, but also on qualitative aspects, aiming to prepare human resources capable of facing future challenges. Growing competition among schools requires effective strategies to recruit competent students. This research applies a qualitative descriptive approach to gain an in-depth understanding of service management strategies. Data were collected through direct observation of the school environment, structured interviews with school leaders, teachers, and members of the new student admissions committee (PPDB), as well as documentation of school programs and activities. Data analysis followed an interactive model, including data reduction, presentation, and conclusion drawing, with triangulation applied to ensure validity. The findings reveal that SMP 3 Tanjungsiang successfully attracts new students through multiple strategies, including enhancing academic and non-academic programs, organizing students into regular and superior classes, and improving extracurricular achievements. Among these, the most influential factor is the performance and coordination of the PPDB committee. These results offer practical guidance for schools seeking to optimize educational service management and student recruitment, particularly in geographically challenging regions.